Cost-efectiveness analysis of integrated community case management delivery models utilizing drug sellers and community health workers for treatment of under-fve febrile cases of malaria, pneumonia, diarrhoea in rural Uganda - Lubogo, Patrick; Lukyamuz, John Edward; Kyambadde, Deo; Komakech, Alex Aboda; Kitutu, Freddy Eric; Mulogo, Edgar Mugema (Malaria journa, 2021)
Background: Malaria, pneumonia and diarrhoea continue to be the leading causes of death in children under the age of fve years (U5) in Uganda. To combat these febrile illnesses, integrated community case management (iCCM) delivery models utilizing community health workers (CHWs) or drug sellers have been implemented. The purpose of this study is to compare the cost-effectiveness of delivering iCCM interventions via drug sellers versus CHWs in rural Uganda. Methods: This study was a cost-effectiveness analysis to compare the iCCM delivery model utilizing drug sellers against the model using CHWs. The effect measure was the number of appropriately treated U5 children, and data on effectiveness came from a quasi-experimental study in Southwestern Uganda and the in SCALE cross-sectional house-hold survey in eight districts of mid-Western Uganda. The iCCM interventions were costed using the micro-costing (ingredients) approach, with costs expressed in US dollars. Cost and effect data were linked together using a decision tree model and analysed using the Amua modelling software. Results: The costs per 100 treated U5 children were US$591.20 and US$298.42 for the iCCM trained-drug seller and iCCM trained-CHW models, respectively, with 30 and 21 appropriately treated children in the iCCM trained-drug seller and iCCM trained-CHW models. When the drug seller arm (intervention) was compared to the CHW arm (control), an incremental effect of 9 per 100 appropriately treated U5 children was observed, as well as an incremental cost of US$292.78 per 100 appropriately treated children, resulting in an incremental cost-effectiveness ratio (ICER) of US$33.86 per appropriately treated U5 patient. Conclusion: Since both models were cost-effective compared to the do-nothing option, the iCCM trained-drug seller model could complement the iCCM trained-CHW intervention as a strategy to increase access to quality treatment
Keywords: Drug sellers; Community health workers (CHWs); Integrated community case management (iCCM)